Features of individual physical development of preschool children - Друзь Валерій Анатолійович (Valeriy Druz); Артем’єва Галина Павлівна (Galina Artem’yeva); Нечитайло Марія Валеріївна (Mariia Nechytailo) (Slobozhanskyi Herald of Science and Sport, 2014)
Purpose: to study and analyze the characteristics of individual physical development of children of preschool age and the age periodization in modern scientific and methodological literature. Material and Methods: analysis and compilation of scientific-methodical and professional literature in order to identify common features of physical development of children of preschool age. Results: questions of periodization age and studied the characteristics of individual physical development children’s of preschool age. Conclusion: the study showed that despite the presence of a large number of scientific and methodological developments of modern scientists devoted to the problems of the physical features of early childhood development, to date, there are no uniform standards for monitoring and evaluation of individual physical development of children of preschool age, which is the basic problem of a correct assessment of the physical child development and requires further investigation.